1990
DOI: 10.1093/ajh/3.1.23
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Delivery Mode on Biological Inactive Renin Level in Umbilical Cord Blood

Abstract: In order to investigate the influence of delivery mode on biological inactive renin levels in fetal circulation, plasma inactive renin (PIR), plasma renin activity (PRA) and plasma total renin (PTR) were measured in umbilical venous blood samples of 21 infants delivered vaginally after spontaneous labor and of 9 infants delivered by elective cesarean section after the onset of labor. Biological renin activities were measured by bioassay. The PIR levels in infants delivered vaginally were significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a further study, though blood pressure at birth was the same, during the first 24 h post partum the blood pressure of the VD infants increased to a greater extent than that of the CS infants, producing a significant difference in blood pressure at 24 h post partum (Gemelli et al , 1992). This finding may be attributable to differences in the renin‐angiotensin‐aldosterone system (Broughton Pipkin et al , 1974; Fujimura et al , 1990; Oliveira Filho & Procianoy, 1995).…”
Section: Short‐term Physiological Changes In Response To Caesarementioning
confidence: 99%
See 1 more Smart Citation
“…In a further study, though blood pressure at birth was the same, during the first 24 h post partum the blood pressure of the VD infants increased to a greater extent than that of the CS infants, producing a significant difference in blood pressure at 24 h post partum (Gemelli et al , 1992). This finding may be attributable to differences in the renin‐angiotensin‐aldosterone system (Broughton Pipkin et al , 1974; Fujimura et al , 1990; Oliveira Filho & Procianoy, 1995).…”
Section: Short‐term Physiological Changes In Response To Caesarementioning
confidence: 99%
“…Two studies report an increase in plasma TSH concentration (Bird et al , 1996; Ramezani Tehrani et al , 2003), although one study found the reverse (Miyamoto et al , 1991); the reason for this discrepancy is unclear and further work is required to establish the dynamics of TSH after different modes of delivery. The plasma concentration of biologically active renin is reduced in CS neonates (Fujimura et al , 1990), possibly as a result of the increase in cord blood pH (Tetlow & Broughton Pipkin, 1983). Consistent with this finding, plasma angiotensin II concentration is reduced ( P = 0.03) in CS neonates (Broughton Pipkin et al , 1974; Kingdom et al , 1993; Lumbers & Reid, 1977).…”
Section: How Might Plcs Account For These Physiological Differences?mentioning
confidence: 99%